Of, The, By Characteristic Analysis of The Novel "Fangirl" By Using Reader Response - Amalia Firda Damayanti; Fitrotuz Zakiah; Wahyu Indah Mala Rohmana (Journal of English Education, Literature and Linguistics, 2023)
This research is an analysis of the personalities of the twin characters named Cath and Wren expressed in Fangirl novel by Rainbow Rowell. This study analyzes the characteristics of twins based on reader response analysis. The researcher found several characteristics in the twin characters including caring, anxious, fearful, impulsive, headstrong, forgiving, enthusiastic, and wisd. The method used in this research is descriptive qualitative method. The main data source comes from novel literature. In addition, as research supporting data, from articles in magazines and the internet. The data collection technique used in this research is document analysis.